Amniotic fluid myeloperoxidase in pregnancies complicated by preterm prelabor rupture of membranes - Kacerovsky, Marian; Tambor, Vojtech; Vajrychová, Marie; Lenco, Juraj; Hornychova, Helena; Musilova, Ivana; Menon, Ramkumar (The journal of maternal-fetal & neonatal medicine, 2013)
OBJECTIVE: To determine amniotic fluid myeloperoxidase concentration in women with preterm prelabor rupture of the membranes with microbial invasion of the amniotic cavity and histological chorioamnionitis. METHODS: One hundred eighty-one women with singleton pregnancies with a gestational age between 24+0 and 36+6 weeks were included in this study. Amniocenteses were performed, and myeloperoxidase concentration in the amniotic fluid was determined using ELISA. RESULT: Women with microbial invasion of the amniotic cavity had higher median myeloperoxidase concentration than women without this condition (149.2 ng/mL vs. 54.6 ng/mL; p = 0.0006). Women with the presence of histological chorioamnionitis had higher median myeloperoxidase concentration than women without histological chorioamnionitis (103.7 ng/mL vs. 50.0 ng/mL; p = 0.0001). The presence of both microbial invasion of the amniotic cavity and histological chorioamnionitis was associated with higher median myeloperoxidase concentration (456.0 ng/mL vs. 52.9 ng/mL; p < 0.0001). The results remained significant after adjusting for gestational age. CONCLUSIONS: Increased amniotic fluid myeloperoxidase in microbial invasion of the amniotic cavity and histological chorioamnionitis confirm a role of myeloperoxidase in preterm prelabor rupture of the membranes pathophysiology.
Keywords: novorozenec; Infant, Newborn; Peroxidase; výsledek těhotenství; Pregnancy; Humans; Premature Birth; Sepsis; kohortové studie; Fetal Membranes, Premature Rupture; gestační stáří; Female; dospělí; ELISA; sepse; Pregnancy Outcome; amniocentéza; peroxidasa; chorioamnionitida; lidé; Amniotic Fluid; Amniocentesis; Enzyme-Linked Immunosorbent Assay; Cohort Studies; Adult; ženské pohlaví; plodová voda; Retrospective Studies; Amnion; těhotenství; Chorioamnionitis; retrospektivní studie; předčasný odtok plodové vody; předčasný porod; Gestational Age; amnion